Life Food Diet: A Protocol for the Promotion of the Mediterranean Diet - Domiziana Giordano; Francesca Rocca; Lucia Giovannelli; Giuseppe Calamusa; Alberto Firenze (Senses and Sciences, 2018)
Background: The potential benefits for the health arising from the Mediterranean Diet (MD) are supported by several scientific evidences: the MD helps to reduce the LDL cholesterol levels, to prevent and/or control conditions dramatically spread out such as diabetes, overweight and obesity. A healthy and balanced diet constitutes an incisive instrument of preventing the chronical diseases, the cardiovascular risk factors and certain cancers. Objectives: The “Life Foof Diet” (LFD) Project is aimed at promoting worldwide the MD, along with all benefits arising out from the latter for the Public Health. The project involves several professionals and sectors, within the context of a multidisciplinary cooperation, in which culture/research and catering/food sector can ensure the quality of the products. Methods: The cooperation among the players operating in the food sector, operators of the catering sector and companies of the entire Mediterranean Sea area, in addition to the endorsement of the Sicily Region shall be required. The certification so-called “Life Food Diet” can be granted to products which complies with the MD and which meet the specific requirements imposed by the applicable regulation.